Secuencia didáctica para la creación de situaciones problema en gestión de datos - Advincula Clemente, Elizabeth (2022)
The purpose of this research is to propose a didactic sequence for practicing elementary school teachers, which will allow them to create problem situations to trigger data management processes. The theoretical framework used is the Statistical Thinking approach in empirical research by Wild and Phannkuch (1999). The basis of our strategy for the creation of problem situations is the first dimension proposed by this approach, the empirical research cycle or PPDAC cycle. The methodology to be used in this research is qualitative and seeks to validate the proposed didactic sequence. We have a first version of the didactic sequence, which will be implemented with a group of teachers who have followed strengthening workshops that include knowledge of the PPDAC cycle. This will allow us to validate the effectiveness of the proposal and make the necessary adjustments in the sequence.